LEVEL OF ASSOCIATION BETWEEN MORPHOLOGICAL, PHYSIOLOGICAL VARIABLES AND HEALTH-RELATED BODY IMAGE WITH THE PRACTICE OF PHYSICAL ACTIVITIES IN MALE AND FEMALE ADULTS IN THE MUNICIPALITY OF NATAL RN (Fiep Bulletin - online, 2015)
The purpose of this study was to analyze the degree of association between morphological and physiological variables of physical aptitude related to health and the level of practice of physical activity and body image in adults of both genders in the Municipality of Natal-RN. The study was transversal analytical. Sample comprised 200 individuals of both genders practicing physical activities within the age group between 20 to 69 years. At the experimental treatment we used morphological variables (Body Weight, WHR, BMI), physiological variables VO2max, RHR, THR, MBP and DBP) and the body image variable. The statistical treatment used the variance analysis test. The level for rejection of hypothesis of nullity was set at 0.05. The association between variables pertaining to health-related morphological and physiological dimensions and the level of practice of physical activity and body image in adults of both genders and in the relevant age groups recorded a significant improvement in the values found in Body Weight, WHR, BMI, VO2max and DBP and in the body image satisfaction index.
Keywords: 1. Physical Activity; 2. Morphological and Physiological Variables; 3. Body Image.